The Muslim brothers in Europe : roots and discourse - Maréchal, Brigitte. (Muslim Minorities, 2008)
This volume provides an overview on the history of the Muslim Brotherhood and the ways its heritage is appropriated by its European members today. They define themselves as the "community of the middle way", in the centre of Islamic orthodoxy, proposing an ethos and an ideology. However their heritage is composed of many different intellectual strata and these inputs are in tension. The current movement is both powerful and fragile as certain fundamental principles remain respected while many other themes are currently being cautiously questioned. By analysing private interviews and public discourse, this book fills in an important gap in scholarly research. No other in-depth study exists about this little known and reserved but important reference for European Muslims.